Oxidation reactions of an anionic gallium(I) N-heterocyclic carbene analogue with group 16 compounds. - BAKER, ROBERT (My University, 2005)
The reactivity of an anionic gallium(I) heterocycle, [K(tmeda)][:Ga([N(Ar)C(H)]2)], Ar = C6H3Pr(i)2-2,6, towards sources of elemental chalcogens and diorgano-dichalcogenides has been investigated and comparisons drawn with the reactivity of the valence isoelectronic N-heterocyclic carbene class of ligand. The reactions of the heterocycle with N2O or (Te)PEt3 yielded the dimeric, dianionic gallium(III) complexes, [K(L)]2[(mu-E)Ga([N(Ar)C(H)]2)]2, E = O, L = tmeda; E = Te, L = THF. Treatment of [K(tmeda)][:Ga([N(Ar)C(H)]2)] with the diphenyl dichalcogenides, PhEEPh, E = Se or Te, gave the one dimensional polymer, [K[(PhSe)2Ga([N(Ar)C(H)]2)]]infinity and the monomeric complex, [K(OEt2)3][(PhTe)2Ga([N(Ar)C(H)]2)], respectively. The X-ray crystal structures of the four complexes are reported.
PUBLISHED
Keywords: Chemistry